Climate-driven vicariance and long-distance dispersal explain the Rand Flora pattern in the liverwort Exormotheca pustulosa (Marchantiophyta). (9th June 2020) - Rodrigues, Ana Sofia Bartolomeu; Martins, Anabela; Garcia, César Augusto; Sérgio, Cecília; Porley, Ron; Fontinha, Susana; González-Mancebo, Juana; Gabriel, Rosalina; Phephu, Nonkululo; Van Rooy, Jacques; Dirkse, Gerard; Long, David; et al.
Abstract: The 'Rand flora' is a biogeographical disjunction which refers to plant lineages occurring at the margins of the African continent and neighbouring oceanic archipelagos. Here, we tested whether the phylogeographical pattern of Exormotheca pustulosa Mitt. was the result of vicariance induced by past climatic changes or the outcome of a series of recent long-distance dispersal events. Two chloroplast markers ( rps 4- trn F region and psb A- trn H spacer) and one nuclear marker (ITS2) were analysed. Phylogenetic and phylogeographical relationships were inferred as well as divergence time estimates and ancestral areas. Exormotheca possibly originated in Eastern Africa during the Late Oligocene/Early Miocene while Exormotheca putulosa diversified during the Late Miocene. Three main E. pustulosa groups were found: the northern Macaronesia/Western Mediterranean, the South Africa/Saint Helena and the Cape Verde groups. The major splits among these groups occurred during the Late Miocene/Pliocene; diversification was recent, dating back to the Pleistocene. Climate-driven vicariance and subsequent long-distance dispersal events may have shaped the current disjunct distribution of E. pustulosa that corresponds to the Rand Flora pattern. Colonization of Macaronesia seems to have occurred twice by two independent lineages. The evolutionary history of E. pustulosa populations of Cape Verde warrants further study.